Recuperação das trocas gasosas e fluorescência da clorofila em plantas de Annona emarginata (Schltdl.) H. Rainer submetidas a estrese hídrico - Mantoan, Luís Paulo Benetti [UNESP] (2013)
The present study aimed to evaluate the recoverability of Annona emarginata (Schltdl.) H. Rainer after water stress through changes in the gas exchange, chlorophyll a fluorescence and antioxidant enzymes activity. The experiment was implanted in a randomized block design with three treatments (Irrigation, Suspension of Irrigation and Rehydration) and four replicates of six plants per plot totaling 24 plants. The following variables were evaluated: relative water content of leaves (RWC), gas exchange (CO2 assimilation, A; stomatal conductance, GS; transpiration, E; internal carbon concentration, Ci; water use efficiency, A/E and carboxylation efficiency, A/Ci), chlorophyll a fluorescence (maximum quantum yield, FV/FM; maximal leaf fluorescence under dark, FM; minimum leaf fluorescence under dark, Fo), antioxidant enzymes (superoxide dismutase, SOD, EC. 1.15.1.1 and peroxidase, POD, EC. 1.11.1.7) and lipid peroxidation. The data were submitted to analysis of variance and means were compared by Tukey test at 5% probability and/or standard deviation. At 38 Day After Treatments Beginning (DATB) (day of rehydration), the RWC in irrigated plants showed 87% reducing to 73% in plants under suspension of irrigation where has been verified null CO2 assimilation. Although the RWC of rehydrated plants has recovered to the level of the plants in the beginning of treatments, gas exchange showed partial recovery. The activity of SOD and POD of both leaves and roots showed recovery after rehydration and no changes were observed in the level of lipid peroxidation in leaves and roots in the three treatments. In the analysis of chlorophyll a fluorescence were not detected damage in the photosystem II and neither changes in the efficiency of the photochemical apparatus in both plants under suspension of irrigation and rehydrated in relation to irrigated. Therefore, even with the recovery of the activity of SOD and POD ...